Cinema as weather : stylistic screens and atmospheric change - McKim, Kristi, 1977- (Routledge advances in film studies, 2013)
How do cinematic portrayals of the weather reflect and affect our experience of the world? While weatherly predictability and surprise can impact our daily experience, the history of cinema attests to the stylistic and narrative significance of snow, rain, wind, sunshine, clouds, and skies. Through analysis of films ranging from The Wizard of Oz to The Umbrellas of Cherbourg, from Citizen Kane to In the Mood for Love, Kristi McKim calls our attention to the ways that we read our atmospheres both within and beyond the movies. Building upon meteorolog.